Firm cyclicality and financial frictions - Alex Clymo; Filip Rozsypal (Danmarks Nationalbank, 2023)
Firms' sensitivities to business cycles differ by size and age. The differences are large: "young and small firms" are more cyclical than large firms, whereas "old and small" firms are closer to acyclical. A heterogeneous-firm model with heterogeneous returns to scale can replicate these findings, and implies changes in the potency of different stabilisation policies.
Keywords: D22; E32; G32; L25; 330; firm age; firm size; cyclicality; financial frictions